Effective Use of E-learning Materials in Medical College Libraries in Karnataka: a Study - Kannappanavar, B. U.; Rajanikanta, S. T. (Journal of Information and Knowledge, 2008)
The paper highlights the use of e-learning resources in medical colleges. Study found that the Medical education popularized only after the independence of the country. It is found that majority of the colleges under the study have e-information resources, e-databases. Almost all colleges under study are also becoming members of a consortium. As for as the infrastructure facilities are concerned almost all colleges under study have provided very good infrastructure facilities to their libraries to serve their client effectively. Further, majority of colleges are also having internet and network facilities.